Remapping race in a global context
1 online resource.
Keywords: "Investigating the reality and significance of racial categories, Remapping Race in a Global Context examines the role of race in human genomics, biomedicine, and struggles for social justice around the world. In this book, biologists, anthropologists, historians, and philosophers inspect critical questions around the biological reality of race and how it has been understood in different national and regional contexts. The essays also examine debates on the usefulness of race in medical and epidemiological studies. With focus on the fields of human genomics and biomedicine, this book presents critical findings on whether and how race might be ethically and epistemologically justified in our age of personalized medicine, mass surveillance, and biased algorithms. The book will be of interest to researchers and advanced students in a broad range of scientific and humanistic disciplines, including biology, anthropology, geography, philosophy, cultural or community studies, critical race theory, and any field concerned with the deep racial dividing lines running across societies globally"--